Combining adhesive nanostructured surfaces and costimulatory signals to increase T Cell activation - Guasch, Judith; Spatz, Joachim P. (Nano letters, 2018)
Adoptive cell therapies are showing very promising results in the fight against cancer. However, these therapies are expensive and technically challenging in part due to the need of a large number of specific T cells, which must be activated and expanded in vitro. Here we describe a method to activate primary human T cells using a combination of nanostructured surfaces functionalized with the stimulating anti-CD3 antibody and the peptidic sequence arginine-glycine-aspartic acid, as well as costimulatory agents (anti-CD28 antibody and a cocktail of phorbol 12-myristate 13-acetate, ionomycin, and protein transport inhibitors). Thus, we propose a method that combines nanotechnology with cell biology procedures to efficiently produce T cells in the laboratory, challenging the current state-of-the-art expansion methodologies.